Living Tasawuf dan Pedagogi Dzikir: Internalisasi Akhlakul Karimah Siswa Sekolah Dasar Islam - Nurlaila Annajwa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Purpose – This study aims to examine how Living Tasawuf functions as a form of spiritual pedagogy in the internalization of akhlakul karimah among Islamic elementary school students. Specifically, the study explores the role of collective dhikr practiced on the first Monday of the month at SDIT X Pamulang as a medium for cultivating students’ moral and spiritual character. Design/methodology/approach – This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving the principal, Islamic education teachers, classroom teachers, dhikr facilitators, students, and parents. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing/verification. Findings – The findings reveal that the collective dhikr ritual is not merely a routine religious activity, but a living spiritual practice that embodies the values of tasawuf within the school culture. Dhikr serves as a spiritual pedagogy through habituation, teacher role modeling, value interpretation, and students’ religious experience. The internalized values include religiosity, discipline, politeness, respect for teachers, patience, gratitude, humility, responsibility, empathy, and self-control. Practical implications – The study suggests that Islamic elementary schools should manage dhikr activities as structured spiritual character-building programs supported by teacher guidance and parental involvement. Originality/value – This study contributes to the discourse on Islamic character education by positioning school-based dhikr as a practice of Living Tasawuf and as a spiritual pedagogical approach for internalizing akhlakul karimah in elementary education.